Job satisfaction and organisational commitment on the relatonship between employees’ corporate social responsibility (CSR) perceptions and Job performance - Malathi, Balakrishnan (2018)
Corporate Social Responsibility (CSR) has in recent years become one of the standard business practices for organizations. Thus, this study aimed to empirically investigate the effects of CSR perceptions on job performance among logistics employees where job satisfaction and organizational commitment play mediating roles on the relationship between CSR perceptions and job performance. Social exchange theory, social identity theory and organizational justice theory were used to explain the relationship between the variables. The respondents of this study were among the employees of ten logistics companies listed on Bursa Malaysia operating in West Malaysia. Purposive sampling method was used. Total of 810 questionnaires were distributed to the respondents. Out of total questionnaire, 432 questionnaires were completed and returned with response rate of 53%. Data were analyzed using Statistical Package for Social Science (SPSS) and Smart Partial Least Square (Smart- PLS) software. The findings revealed that CSR perception had a non-significant relationship with job performance. Meanwhile, job satisfaction had no significant influence on job performance but organizational commitment had a positive and significant influence on job performance. Besides, job satisfaction and organizational commitment were found to significantly mediate the relationship between CSR perceptions and job performance. This study suggests several practical methods for managers in logistics companies to implement CSR practices in their organizations to enhance employees’ organizational commitment and job satisfaction which, in turn, will improve their job performance. Furthermore, the development and implementation of CSR strategies can help business organisations to achieve competitive advantage, enhance reputation to attract and retain talented employees and also improve business opportunities. Hopefully, this study provides a platform to widen the scope of studies regarding the relationship between CSR and job performance in the logistics field particularly from the perspectives of employees.